EXPERIMENTAL STUDY ON ENGINEERED GEOPOLYMER COMPOSITES WITH BASIC OXYGEN FURNACE SLAG - Zhanguatov, Nuradil (Nazarbayev University School of Engineering and Digital Sciences, 2025)
High-performance and sustainable construction materials have been given growing consideration in recent times, driven by the necessity to minimize the environmental impact of construction operations without sacrificing structural performance. The study explores the feasibility of utilizing Basic Oxygen Furnace Slag (BOFS) as a substitute fine aggregate in Engineered Geopolymer Composites (EGC) by examining the mechanical and durability characteristics of the material. The motivation for this study is the twofold benefit of sustainability and enhanced material performance. By utilizing BOFS as a substitute for natural sand, industrial waste can be recycled, reducing landfill disposal while reducing the depletion of natural resources. Furthermore, the replacement of the OPC in the matrix by a geopolymer binder saves carbon dioxide emission to a great extent, which is also in conformity with global sustainability efforts. The research aims to evaluate the influence of BOFS content and alkaline activator proportions on fresh, mechanical, durability properties and strain-hardening behavior of the EGC blends. The experimental work involved the preparation of a range of EGC mixes using low- calcium fly ash (FA), ground granulated blast furnace slag (GGBFS), and BOFS as fine aggregate. Three ratios of alkaline activators (1.5, 2.0, and 2.5) were investigated to analyze their effect on the geopolymerization process and also on the mechanical properties. A comprehensive testing regime was adopted to analyze workability in the fresh state, hardened properties, durability properties, and strain-hardening indices. The strain hardening behavior was evaluated according to energy and strength parameters, wherein tensile behavior was examined using dog-bone-shaped samples and fracture toughness via notched beam tests. The minimum values for pseudo strain hardening behavior were met by most of the mixtures, but mixture with 1.5 activator ratio and 100% BOFS substitution did not correspond to ductile behavior because of the strain capacity being below the limit. The results indicate that BOFS content significantly influences mechanical performance. Although compressive strength remained constant or was slightly improved by the incorporation of BOFS, tensile strain capacity and flexural strength decreased with higher BOFS content. An activator ratio of 1.5 and a moderate degree of BOFS replacement resulted in the optimum strength-ductility balance. However, only the 1.5R_B100 mixture (100% BOFS substitution) did not meet the minimum strain capacity limit (1.5%), which proved that full substitution could hinder strain-hardening performance because of potential interfacial transition zone (ITZ) weakening. Durability testing showed that drying shrinkage was reduced by BOFS incorporation and length change values were in the acceptable range for alkali silica reaction (ASR) and water expansion tests. Additionally, the study demonstrated that the reaction between geopolymer and BOFS mitigates the detrimental expansion effect of cement and BOFS reaction. But high activator ratios (2.0 and 2.5) caused instability of the geopolymer matrix that detrimentally affected the long-term strength gain. The results indicate that EGC mixed with BOFS is a viable sustainable and ductile construction material, but additional studies are necessary to optimize activator compositions, improve fiber-matrix bonding, and conduct other durability tests like freeze-thaw tests.
Keywords: type of access: embargo; Geopolymer composite; Strain-hardening; Basic Oxygen Furnace slag; Durability; Sustainability